Tracheotomy/Tracheostomy Management at Home and in Care Centers - Guillaume Buiret; Laura Gautheron; Hélène Labrosse-Canat (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2016)
Aim and objectives: Formalize a consensus about patient's care management (nursing techniques, management of complications) with tracheotomy or tracheostomy at home and in care center. Background: Tracheotomy and tracheostomy are medical devices used for many years thus inspiring fear mainly by their symbolic impacts and the lack of training of health professionals.  Design: This study is a mixed research with a qualitative methodology including iterative focus groups.  Methods: A national call for project was performed on Internet to recruit multi-professional volunteers early 2015, anyone was accepted. Seven phone call with focus groups, each 2 hours, were set during 2015. Finally the project was presented and validated in "Guidelines and French Oncology Networks" J2R congress in Nantes, France in December 2015 and published on the web.  Results: Definitions, anatomic and physiologic notions, then the different types of cannulas are presented in the document. The management of tracheotomy/tracheostomy daily cares with protocols and videos, of the complications (infections, bleeding ...), of functional sequelae (phonation, swallowing) at home and in care centers is then explained and demonstrated. Conclusions: Finally, this work has led to a national consensus on the management, at home and in care centers, of tracheotomy and tracheostomy management and their potential complications.  Relevance to clinical practice: Such a work has never been done before. It aims to be comprehensive and didactic by means of figures and decision trees. This study will be useful and could be implemented despite local habits.